Diskursus Uang dalam Kitab Ihya’ Ulum al-Din Karya Al-Ghazali - Muhamad Masrur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
This research investigates the concept of money according to al-Ghazali in IhyaUlum al-Dinas well astherelevance of the money concept of al-Ghazali with contemporary economic system.This research used qualitative approach and based on library research. The result of this research found that the concept of money cannot be separated by ethical values. While its relevance to the contemporary economic system is the return of the function of money in al-Ghazali’s view as a medium of exchange not as a commodity tool and it is possible to be applied monetary system of dinar and dirham